Orientalism and the issue of Iraq’s women’s movement: challenges and reflections - Cassol, Luiza; Dall'Áqua, Maria Eduarda; Chiuza, Sabrina (Malala, 2020)
This paper analyses the limitations and challenges that Orientalist discourse promoted by the West presents to the interpretation of Iraqi women and their movements, and how it overshadows their historical political participation in the country. This is done through a news’ discourse analysis of 5 broadcasters in the U.S. discoursing over postinvasion Iraq (2003-2013) and how it brings out an orientalist discourse that sets forth an arab woman stereotype and their need of external interference.